Pharmaceutical emulsions : a drug developers toolbag - Sarker, Dipak K. (Wiley Blackwell, 2013)
Pharmaceutical Emulsions: A Drug Developer's Toolbag covers all the key aspects of pharmaceutical emulsions, starting from the fundamental scientific basics, to the pharmaceutical forms and the chemical tests for its application. The author uses his extensive experience in both industry and academic experience to provide a concise, student friendly guide to the essential fundamentals of physical pharmacy. Divided into three clear sections, the text begins with Section A - Consideration for Product: Medicinal Formulation which includes a historical perspective, explanation of wha.